1886 Gen and Local Acts of the State of Ohio 99-100, ch. 4, § 3079 (vol. 83) - (:unkn) unknown (General Publisher, 1886)
if any person shall temporarily erect any stand, booth, or other structure for the purpose of exposing for sale, giving, bartering, or otherwise dispose of any spirituous or other intoxicating liquors whatsoever, at or within a distance of one mile from any such parade or encampment, he may be put immediately under guard, and kept at the discretion of the commanding officer, and such commanding officer may turn over such person to any police officer or constable of the city, township or town wherein such duty, parade or drill, encampment or meeting is held, for examination or trial before any court of justice having jurisdiction of the place."
--
Keywords: ARMED FORCES